PENGARUH SOAL HOTS TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA KELAS VII PADA MATERI HIMPUNAN - Muhamad Syahdan Sa'id; Burhanul Aqil; Ibrahim Ibrahim (INSPIRAMATIKA, 2022)
Education has a very important role in improving the quality and quality of Human Resources. Education today is needed as a provision in developing 21st century competencies which include the competence to think, act, and live in the world. Mathematics can improve the ability to think critically, logically, and creatively in a person so it is important to learn. Critical thinking ability is an effort made by someone to get more meaningful knowledge. One of the assessment instruments that can be used to measure students' critical thinking skills is the HOTS (High Order Thinking Skills) question. This study aims to measure the level of mathematical critical thinking skills of class VII students on the set material. The method used in this research is a survey method and uses quantitative research. The sample of this research is students of class VII B and VII C of MTs Negeri 9 Bantul. The data collection technique used in this research is using a questionnaire or a questionnaire and a test instrument. The result of this research is that the average HOTS score is 58.4 and the average questionnaire result is 64.9. So it can be said that the mathematical critical thinking ability of grade VII students of MTs Negeri 9 Bantul is in the medium category.